Medical professional perception, attitude, knowledge, and experience about child abuse and neglect in Bagalkot district of north Karnataka: A survey report - S V Kirankumar; H Noorani; P K Shivprakash; S Sinha (Wolters Kluwer Medknow Publications, 2011)
Aims: The aim of this study was to analyze medical professional, perception, attitude, knowledge, and experience about child abuse and neglect in Bagalkot district, north Karnataka, India. Materials and Methods: Two hundred medical professional, working in both public and private sectors in the province were interviewed by a single operator. Descriptive analyses were carried out by using the obtained data. Results: Medical professional's perception about child abuse and neglect (CAN) is low and these professionals have poor attitude and knowledge toward CAN in accordance with the code of conduct and law. The available information and education is also poor. Conclusions: The results obtained from the study showed that there is lack of knowledge and poor attitude and perception about CAN among medical professionals that prevents them from detecting and identifying suspected cases. Continuing medical education is required to enhance the ability of professionals to detect CAN cases.